2021
DOI: 10.33394/jk.v7i1.3006
|View full text |Cite
|
Sign up to set email alerts
|

Does Compensation Important? The Effect of Compensation on Teachers Performance in Vocational High School

Abstract: The purpose of this study was to determine the effect of compensation on the teacher performance in vocational school. This research used a quantitative approach. Data collection technique was by distributing a questionnaire using a five-likert scale. The sampling technique used was cluster random sampling. Samples taken from each school amounted to 3 teachers from each department, so there were 42 respondents from 5 schools. Validity test used the Pearson product moment. The analysis technique used to answer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Financial compensation also positively and significantly affects lecturer professionalism (Idris et al, 2017). The results of other studies contradict that the compensation given to teachers is overall unsatisfactory because many teachers feel uncomfortable with the existing compensation packages and policies (Wekesa, 2013). Some research findings also report the effect of professional allowances on teacher performance conducted by Kartini (2019), who found that professional allowances had a significant effect in Muara Sugihan District.…”
Section: Introductionmentioning
confidence: 96%
“…Financial compensation also positively and significantly affects lecturer professionalism (Idris et al, 2017). The results of other studies contradict that the compensation given to teachers is overall unsatisfactory because many teachers feel uncomfortable with the existing compensation packages and policies (Wekesa, 2013). Some research findings also report the effect of professional allowances on teacher performance conducted by Kartini (2019), who found that professional allowances had a significant effect in Muara Sugihan District.…”
Section: Introductionmentioning
confidence: 96%